A pa6 nylon composition for short fiber fabric and a method for preparing the same
Patent Information
- Application Number
- CN202611266274.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-09
AI Technical Summary
[0003]现有二氧化钛浆料中的分散剂通常以物理吸附方式附着于颗粒表面,当浆料由水相转入己内酰胺体系并经历高温聚合时,原有分散层容易发生脱附或失稳,使二氧化钛颗粒重新聚集,形成较大的团聚颗粒,进而影响其在PA6中的均匀分布
[0025]本申请通过二氧化碳酸化、6-氨基己酸吸附及氨气碱化再分散的顺序处理,在钛白粉表面形成与PA6体系相容的吸附层,并采用挥发性物质调节pH,减少无机离子残留;所得表面改性钛白粉水分散液不经分离和干燥而直接与己内酰胺共同聚合,可减少钛白粉二次团聚,使其较均匀地分散于PA6树脂中,从而提高PA6组合物的聚合及纺丝稳定性,使所得短纤具有均匀完整的近十字形截面和较好的力学性能。
Smart Images

Figure CN122878744A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of nylon composition technology, and in particular to a PA6 nylon composition for short fiber fabrics and its preparation method. Background Technology
[0002] Nylon 6 (PA6) possesses high strength, good abrasion resistance, and excellent spinnability, making it widely used in the production of nylon staple fibers and fabrics. To reduce the transparency and surface gloss of PA6 fibers, anatase titanium dioxide is typically added as a matting agent during caprolactam polymerization. Current processes generally involve first preparing an aqueous slurry of titanium dioxide, then adjusting the slurry's pH, adding dispersants, or surface-treating the titanium dioxide to allow it to enter the polymerization system along with caprolactam. Due to the small particle size, large specific surface area, and hydroxyl groups on the surface of titanium dioxide, adsorption and agglomeration easily occur between particles due to their high surface energy.
[0003] In existing titanium dioxide slurries, dispersants are usually attached to the particle surface by physical adsorption. When the slurry is transferred from the aqueous phase to the caprolactam system and undergoes high-temperature polymerization, the original dispersion layer is prone to desorption or instability, causing the titanium dioxide particles to re-aggregate and form larger agglomerates, which in turn affects their uniform distribution in PA6. Summary of the Invention
[0004] The present invention provides a PA6 nylon composition for short fiber fabrics, comprising PA6 resin and surface-modified titanium dioxide dispersed in the PA6 resin, wherein the titanium dioxide accounts for 2% of the total mass of the PA6 nylon composition.
[0005] It should be noted that the surface-modified titanium dioxide is distributed as a dispersed phase in PA6 resin. One end of the 6-aminohexanoic acid on its surface is bonded to the titanium dioxide, while the other end forms hydrogen bonds with the PA6 molecular chain or participates in the amidation reaction, thereby forming an interfacial transition layer and reducing titanium dioxide agglomeration. When the titanium dioxide content is 2%, sufficient light scattering centers can be formed, while also taking into account the spinning stability of PA6.
[0006] As a preferred technical solution for PA6 nylon compositions used in short-fiber fabrics, the titanium dioxide is anatase titanium dioxide.
[0007] It should be noted that anatase titanium dioxide has suitable light scattering ability and lower hardness than rutile titanium dioxide, which can reduce wear on spinning equipment and spinnerets while achieving matting.
[0008] In addition, this application provides a method for preparing a PA6 nylon composition for short-fiber fabrics, comprising the following steps:
[0009] S1. Mix titanium dioxide and water, with the total mass of titanium dioxide and water being 100%, the mass percentage of titanium dioxide being 30% and the mass percentage of water being 70%, and stir at 60°C to obtain a titanium dioxide aqueous dispersion system;
[0010] S2. Carbon dioxide is introduced into the titanium dioxide aqueous dispersion system to adjust the pH of the titanium dioxide aqueous dispersion system to 4.5-5.2; 0.3%-0.8% of 6-aminohexanoic acid by mass of the titanium dioxide is added, and adsorption treatment is carried out at 60°C.
[0011] S3. Stop the carbon dioxide flow, introduce ammonia into the adsorption-treated titanium dioxide aqueous dispersion system, adjust its pH to 8.0-9.0, and then perform shear dispersion to obtain surface-modified titanium dioxide aqueous dispersion.
[0012] S4. Before the caprolactam starts heating, the surface-modified titanium dioxide aqueous dispersion is added to the caprolactam polymerization reactor. The amount of the surface-modified titanium dioxide aqueous dispersion added is determined according to 2% of the total mass of the titanium dioxide in the PA6 nylon composition. The surface-modified titanium dioxide aqueous dispersion and caprolactam are heated together and polymerized at 260°C to obtain the PA6 polymer.
[0013] S5. The PA6 polymer is sequentially pelletized, extracted, and dried to obtain the PA6 nylon composition.
[0014] It should be noted that, firstly, titanium dioxide is prepared into an aqueous dispersion system with a solid content of 30%. This ensures the fluidity of the slurry while increasing the contact probability between titanium dioxide and 6-aminohexanoic acid, and promotes molecular diffusion and interfacial adsorption at 60℃. Subsequently, carbon dioxide is introduced to adjust the pH to 4.5–5.2, so that 6-aminohexanoic acid exists in the form of zwitterions and some carboxyl groups. Its carboxyl groups or carboxyl groups are conducive to hydrogen bonding, adsorption, or coordination with the hydroxyl groups and titanium sites on the surface of titanium dioxide, so that 6-aminohexanoic acid is bound to the particle surface. After adsorption is completed, ammonia is introduced to adjust the pH to 8.0–9.0, changing the ionization state of titanium dioxide and its surface modified layer. Combined with shearing action, this breaks down the loose aggregates formed in the acidic adsorption stage, allowing electrostatic repulsion and hydration protection to re-establish between particles. Carbon dioxide and ammonia can escape during subsequent heating, thus reducing non-volatile salt impurities introduced by inorganic acids and alkalis. The resulting dispersion is added directly to the caprolactam polymerization reactor without washing, solid-liquid separation, or drying, avoiding loss of surface modifiers and the formation of hard agglomerates that are difficult to re-dissociate from titanium dioxide during drying. During the ring-opening polymerization of caprolactam, 6-aminohexanoic acid and the repeating structural unit of PA6 have homologous structures. Its exposed amino and / or carboxyl groups can participate in amidation and molecular chain growth, or form hydrogen bonds with the PA6 amide groups, thereby forming an interfacial transition layer between titanium dioxide and PA6 resin. This transforms the temporary physical dispersion of titanium dioxide, which depends on mechanical shear, into an interfacial fixed dispersion that can be maintained during polymerization and subsequent melt spinning.
[0015] In a preferred embodiment of a method for preparing a PA6 nylon composition for short-fiber fabrics, in step S2, after adding the 6-aminocaproic acid, the mixture is stirred at 60°C for 60–120 min.
[0016] It should be noted that stirring at 60℃ for 60–120 min is beneficial for 6-aminohexanoic acid to fully diffuse to the surface of titanium dioxide and complete adsorption or coordination, while avoiding excessive processing time that would reduce process efficiency.
[0017] In a preferred embodiment of a method for preparing a PA6 nylon composition for short fiber fabrics, in step S3, the rotation speed of the shear dispersion is 1000-2000 r / min, and the shear dispersion time is 20-40 min.
[0018] It should be noted that shearing at 1000–2000 r / min for 20–40 min can dissociate the loose aggregates formed during the adsorption process, while taking into account both dispersion efficiency and slurry stability.
[0019] As a preferred technical solution for the preparation method of PA6 nylon composition for short fiber fabrics, the surface-modified titanium dioxide aqueous dispersion obtained in step S3 is directly added to the caprolactam polymerization reactor without solid-liquid separation and drying.
[0020] It should be noted that the surface-modified titanium dioxide aqueous dispersion is used directly for polymerization without solid-liquid separation and drying, which can avoid the loss of modifier and the formation of hard agglomerates that are difficult to redisperse during the dehydration and drying process of titanium dioxide.
[0021] In a preferred embodiment of a method for preparing a PA6 nylon composition for short-fiber fabrics, in step S4, the polymerization temperature is 260°C, and the maximum temperature of the material during polymerization is below 270°C.
[0022] It should be noted that 260℃ can meet the temperature requirements for caprolactam ring-opening polymerization and molecular chain growth, while controlling the maximum temperature of the material below 270℃ can reduce PA6 thermal degradation, yellowing and viscosity decrease.
[0023] In a preferred embodiment of a method for preparing a PA6 nylon composition for short fiber fabrics, in step S5, a hot air circulation method is used for drying, the drying temperature is 85-110℃, the drying time is 5-6h, and the moisture content of the dried PA6 chips is not higher than 0.02%.
[0024] It should be noted that by using hot air circulation drying at 85-110℃ for 5-6 hours, the moisture content of PA6 chips can be reduced to below 0.02%, thereby reducing viscosity decrease, bubbles, and fiber breakage caused by hydrolysis and water vapor escape during subsequent melt spinning.
[0025] This application employs a sequential process of carbon dioxide acidification, 6-aminohexanoic acid adsorption, and ammonia alkalization redispersion to form an adsorption layer compatible with the PA6 system on the surface of titanium dioxide. Volatile substances are used to adjust the pH and reduce inorganic ion residues. The resulting surface-modified titanium dioxide aqueous dispersion is directly co-polymerized with caprolactam without separation and drying, which reduces secondary agglomeration of titanium dioxide and allows it to be more uniformly dispersed in PA6 resin. This improves the polymerization and spinning stability of the PA6 composition, resulting in short fibers with a uniform and complete near-cross-shaped cross section and good mechanical properties. Attached Figure Description
[0026] Figure 1 The images shown are scanning electron microscope images of the near-cross-shaped PA6 short fibers obtained in Example 1 and Comparative Example 1. Figure 1 (a) shows the longitudinal surface morphology of the fiber in Example 1. Figure 1 (b) shows the cross-sectional morphology of the fiber in Example 1. Figure 1 (c) shows the longitudinal surface morphology of the fiber in Comparative Example 1. Figure 1 (d) shows the cross-sectional morphology of the fiber in control example 1.
[0027] Figure 2 The following are DSC curves for Example 1 and Comparative Example 1, wherein... Figure 2 (a) is the secondary heating curve. Figure 2 (b) is the cooling crystallization curve. Detailed Implementation
[0028] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.
[0029] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.
[0030] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.
[0031] Example 1
[0032] This embodiment provides a method for preparing a PA6 nylon composition for short-fiber fabrics, comprising the following steps:
[0033] S1. Add 2.00 kg of anatase titanium dioxide and 4.67 kg of deionized water to a dispersion container, stir at 300 r / min, raise the system temperature to 60℃, and continue stirring for 30 min to obtain a titanium dioxide aqueous dispersion system with a titanium dioxide mass percentage of 30%.
[0034] S2. Under continuous stirring at 60℃, carbon dioxide was slowly introduced into the titanium dioxide aqueous dispersion system. The pH was monitored online using a temperature-compensated pH electrode. After the pH of the system reached 4.5, 6g of 6-aminocaproic acid was added, and stirring was continued at 60℃ for 60min. During the adsorption treatment, carbon dioxide was intermittently introduced to maintain the pH of the system at 4.5-4.6.
[0035] S3. Stop the carbon dioxide supply and slowly introduce ammonia into the adsorption-treated titanium dioxide aqueous dispersion system to adjust the pH of the system to 8.0. Then, use a high-speed shear disperser to shear and disperse at a speed of 1000 r / min for 20 min to obtain the surface-modified titanium dioxide aqueous dispersion.
[0036] S4. Calculate the amount of caprolactam to be added based on the final dry yield of PA6 resin, and add caprolactam to the polymerization reactor. Before the caprolactam starts to heat up, add the surface-modified titanium dioxide aqueous dispersion obtained in step S3 directly to the polymerization reactor without solid-liquid separation, washing and drying. Heat it together with caprolactam under nitrogen protection and polymerize at 260℃ for 5 hours. The maximum temperature of the material during the polymerization process is controlled at 265℃ to obtain PA6 polymer.
[0037] S5. The PA6 polymer is extruded and cut into PA6 slices with a particle size of 2-3 mm. Extraction is performed using hot water at 95°C with a water-to-PA6 slice mass ratio of 4:1 and an extraction time of 8 h to remove unreacted caprolactam and oligomers. After extraction, the PA6 nylon composition is dried at 85°C for 6 h using hot air circulation to obtain a water content of no more than 0.02%.
[0038] Example 2
[0039] This embodiment provides a method for preparing a PA6 nylon composition for short-fiber fabrics, comprising the following steps:
[0040] S1. Add 2.00 kg of anatase titanium dioxide and 4.67 kg of deionized water to a dispersion container, stir at 300 r / min, raise the system temperature to 60℃, and continue stirring for 30 min to obtain a titanium dioxide aqueous dispersion system with a titanium dioxide mass percentage of 30%.
[0041] S2. Under continuous stirring at 60℃, carbon dioxide was slowly introduced into the titanium dioxide aqueous dispersion system. After the pH of the system reached 4.7, 9g of 6-aminocaproic acid was added, and stirring was continued at 60℃ for 80min. During the adsorption treatment, carbon dioxide was intermittently introduced to maintain the pH of the system at 4.6-4.8.
[0042] S3. Stop the carbon dioxide supply and slowly introduce ammonia into the adsorption-treated titanium dioxide aqueous dispersion system to adjust the pH of the system to 8.3. Then, use a high-speed shear disperser to shear and disperse at a speed of 1300 r / min for 25 min to obtain the surface-modified titanium dioxide aqueous dispersion.
[0043] S4. Calculate the amount of caprolactam to be fed based on the final dry yield of PA6 resin. Before the caprolactam starts to heat up, add the surface-modified titanium dioxide aqueous dispersion obtained in step S3 directly into the polymerization reactor without solid-liquid separation, washing and drying. Heat it together with caprolactam under nitrogen protection and polymerize at 260℃ for 5 hours. The maximum temperature of the material during the polymerization process is controlled at 266℃ to obtain PA6 polymer.
[0044] S5. The PA6 polymer is extruded and cut into PA6 slices with a particle size of 2-3 mm. Extraction is performed using hot water at 95℃, with a water-to-PA6 slice mass ratio of 4:1 and an extraction time of 8 h. After extraction, the PA6 nylon composition is dried at 90℃ for 6 h using hot air circulation to obtain a PA6 nylon composition with a water content of no more than 0.02%.
[0045] Example 3
[0046] This embodiment provides a method for preparing a PA6 nylon composition for short-fiber fabrics, comprising the following steps:
[0047] S1. Add 2.00 kg of anatase titanium dioxide and 4.67 kg of deionized water to a dispersion container, stir at 300 r / min, raise the system temperature to 60℃, and continue stirring for 30 min to obtain a titanium dioxide aqueous dispersion system with a titanium dioxide mass percentage of 30%.
[0048] S2. Under continuous stirring at 60℃, carbon dioxide was slowly introduced into the titanium dioxide aqueous dispersion system. After the pH of the system reached 5.0, 13g of 6-aminocaproic acid was added, and stirring was continued at 60℃ for 100min. During the adsorption treatment, carbon dioxide was intermittently introduced to maintain the pH of the system at 4.9-5.1.
[0049] S3. Stop the carbon dioxide flow and slowly introduce ammonia into the adsorption-treated titanium dioxide aqueous dispersion system to adjust the pH of the system to 8.7. Then, use a high-speed shear disperser to shear and disperse at a speed of 1700 r / min for 35 min to obtain the surface-modified titanium dioxide aqueous dispersion.
[0050] S4. Calculate the amount of caprolactam to be fed based on the final dry yield of PA6 resin. Before the caprolactam starts to heat up, add the surface-modified titanium dioxide aqueous dispersion obtained in step S3 directly into the polymerization reactor without solid-liquid separation, washing and drying. Heat it together with caprolactam under nitrogen protection and polymerize at 260℃ for 5 hours. The maximum temperature of the material during the polymerization process is controlled at 268℃ to obtain PA6 polymer.
[0051] S5. The PA6 polymer is extruded and cut into PA6 slices with a particle size of 2-3 mm. Extraction is performed using hot water at 95℃, with a water-to-PA6 slice mass ratio of 4:1 and an extraction time of 8 h. After extraction, the PA6 nylon composition is dried at 100℃ for 5.5 h using hot air circulation to obtain a PA6 nylon composition with a water content of no more than 0.02%.
[0052] Example 4
[0053] This embodiment provides a method for preparing a PA6 nylon composition for short-fiber fabrics, comprising the following steps:
[0054] S1. Add 2.00 kg of anatase titanium dioxide and 4.67 kg of deionized water to a dispersion container, stir at 300 r / min, raise the system temperature to 60℃, and continue stirring for 30 min to obtain a titanium dioxide aqueous dispersion system with a titanium dioxide mass percentage of 30%.
[0055] S2. Under continuous stirring at 60℃, carbon dioxide was slowly introduced into the titanium dioxide aqueous dispersion system. After the pH of the system reached 5.2, 16g of 6-aminocaproic acid was added, and stirring was continued at 60℃ for 120min. During the adsorption treatment, carbon dioxide was intermittently introduced to maintain the pH of the system at 5.1-5.2.
[0056] S3. Stop the carbon dioxide flow and slowly introduce ammonia into the adsorption-treated titanium dioxide aqueous dispersion system to adjust the pH of the system to 9.0. Then, use a high-speed shear disperser to shear and disperse at a speed of 2000 r / min for 40 min to obtain the surface-modified titanium dioxide aqueous dispersion.
[0057] S4. Calculate the amount of caprolactam to be fed based on the final dry yield of PA6 resin. Before the caprolactam starts to heat up, add the surface-modified titanium dioxide aqueous dispersion obtained in step S3 directly into the polymerization reactor without solid-liquid separation, washing and drying. Heat it together with caprolactam under nitrogen protection and polymerize at 260℃ for 5 hours. The maximum temperature of the material during the polymerization process is controlled at 269℃ to obtain PA6 polymer.
[0058] S5. The PA6 polymer is extruded and cut into PA6 slices with a particle size of 2-3 mm. Extraction is performed using hot water at 95℃, with a water-to-PA6 slice mass ratio of 4:1 and an extraction time of 8 h. After extraction, the PA6 nylon composition is dried at 110℃ for 5 h using hot air circulation to obtain a PA6 nylon composition with a water content of no more than 0.02%.
[0059] The following comparative examples are all based on Example 1. Except for the explicitly changed technical features, the amounts of titanium dioxide and water, shear conditions, the content of titanium dioxide in the final composition, caprolactam polymerization conditions, extraction conditions and drying conditions are the same as in Example 1.
[0060] Comparative Example 1: No 6-aminocaproic acid added
[0061] The difference between this comparative example and Example 1 is that in step S2, carbon dioxide is introduced into the titanium dioxide aqueous dispersion system and the pH is adjusted to 4.5, but 6-aminohexanoic acid is not added, and the mixture is directly stirred at 60°C for 60 min; subsequently, ammonia is introduced according to step S3 of Example 1 to adjust the pH to 8.0, and the mixture is sheared and dispersed at 1000 r / min for 20 min. The resulting titanium dioxide aqueous dispersion is added directly to the caprolactam polymerization reactor without solid-liquid separation and drying, and the remaining polymerization, pelletizing, extraction, and drying steps are the same as in Example 1.
[0062] Comparative Example 2: No carbon dioxide acidification adsorption was performed.
[0063] The difference between this comparative example and Example 1 is that in step S2, carbon dioxide is not introduced into the titanium dioxide aqueous dispersion system, nor is the pH of the system adjusted to 4.5. Instead, 6g of 6-aminohexanoic acid is directly added to the titanium dioxide aqueous dispersion system at 60°C and stirred for 60min. Subsequently, ammonia gas is introduced to adjust the pH of the system to 8.0, and the dispersion is sheared at 1000r / min for 20min. The resulting dispersion is used directly for caprolactam polymerization without solid-liquid separation and drying. The remaining steps are the same as in Example 1.
[0064] Comparative Example 3: No ammonia alkalization and redispersion were performed.
[0065] The difference between this comparative example and Example 1 is that, following step S2 of Example 1, the aqueous dispersion system of titanium dioxide was adjusted to pH 4.5, 6g of 6-aminohexanoic acid was added, and adsorption treatment was carried out at 60°C for 60 min. Carbon dioxide was then stopped, but ammonia was not introduced to adjust the pH. The dispersion was directly sheared at 1000 r / min for 20 min under pH 4.5–4.6 conditions. The resulting dispersion was added directly to the caprolactam polymerization reactor without solid-liquid separation and drying. The remaining steps were the same as in Example 1.
[0066] Comparative Example 4: pH adjustment using hydrochloric acid and sodium hydroxide
[0067] The difference between this comparative example and Example 1 is that in step S2, 0.1 mol / L hydrochloric acid was used instead of carbon dioxide to adjust the pH of the titanium dioxide aqueous dispersion system to 4.5, and 6 g of 6-aminohexanoic acid was added and stirred at 60°C for 60 min; in step S3, 0.1 mol / L sodium hydroxide solution was used instead of ammonia to adjust the pH of the system to 8.0, and then sheared at 1000 r / min for 20 min. The resulting dispersion was used directly for caprolactam polymerization without solid-liquid separation and drying, and the remaining steps were the same as in Example 1.
[0068] Preparation of application products
[0069] Three batches of PA6 nylon compositions were prepared independently for Examples 1-4 and Comparative Examples 1-4, respectively. Each batch of PA6 nylon compositions was individually numbered and not mixed. 10 kg of PA6 chips were randomly selected from each batch of PA6 nylon compositions, and near-cross-shaped PA6 staple fibers, PA6 staple fiber yarns, and 100% nylon staple fiber fabrics were prepared according to the following methods.
[0070] S1. Place the PA6 chips in a hot air circulating dryer and dry them at 90°C for 6 hours until the moisture content is no higher than 0.02%. After drying, seal the PA6 chips and transport them to the melt spinning equipment using dry nitrogen.
[0071] S2. The same melt spinning equipment and the same nitrided Inconel 718 near-cross spinneret are used. The spinneret has 300 near-cross-shaped spinneret holes of the same size. The surface roughness Ra of the spinneret is not higher than 0.03μm, and the size tolerance of the spinneret holes is ±0.5μm. The spinning equipment is preheated for 6 hours. The dried PA6 chips are added to the extruder for melting. The temperature zones of the extruder are set to 245℃, 255℃, 260℃ and 265℃ respectively. The temperature of the PA6 melt entering the spinneret is controlled to be 265℃±0.5℃, the spinning pressure is 16MPa±0.2MPa, the melt output per hole is 0.43g / min, and the initial fiber take-up speed is 800m / min.
[0072] S3. The molten fine stream extruded from the spinneret is cooled by a ring blower at a temperature of 17℃±1℃ and a wind speed of 0.60m / s±0.05m / s. The cooled and solidified nascent fibers are bundled together and PA6 spinning oil is applied evenly to make the fiber oil content 0.6%. Then, they are drawn in a 70℃ hot water bath with a total draw ratio of 3.2 times, mechanically crimped to make the crimp number 10 / cm, and heat-set at 100℃ for 20 minutes. Finally, they are cut into near-cross-shaped PA6 short fibers with a length of 38mm and a single fiber linear density of 1.67dtex.
[0073] S4. Each batch of PA6 staple fiber was placed in an environment with a temperature of 20℃ and a relative humidity of 65% for 24 hours to equilibrate, and then sequentially processed by opening, carding, two-stage drawing, roving, and ring spinning. The relative humidity in the spinning workshop was controlled at 85%. During the opening process, an antistatic agent aqueous solution with a mass concentration of 0.9% was sprayed, and the spraying amount was 0.5% of the mass of PA6 staple fiber. The linear density of the obtained PA6 staple fiber yarn was controlled to be 20 tex, the twist direction was Z twist, and the twist was 650 twists / m. Each independent batch produced no less than 5 kg of PA6 staple fiber yarn.
[0074] S5. Each batch of PA6 staple fiber yarn was used as the warp and weft yarn, respectively, and woven into plain weave 100% nylon staple fiber fabric using the same rapier loom. The warp density was 260 threads / 10cm, the weft density was 220 threads / 10cm, the fabric width was 50cm, and the woven length of each batch was not less than 5m. No sizing was applied during the weaving process, and the woven fabric was not dyed, softened, coated, or otherwise finished. 100% nylon staple fiber fabric made from the PA6 nylon compositions of Examples 1-4 and Comparative Examples 1-4 were obtained respectively.
[0075] Product performance testing
[0076] Each independent batch of Examples 1-4 and Control Examples 1-4 was sampled separately, and the results were expressed as the average of the test results of the three independent batches, and the standard deviation was calculated.
[0077] 1. Moisture content of PA6 slices
[0078] After each batch of PA6 slices has completed step S5 drying and before undergoing a second uniform drying, approximately 1.0g of slices is randomly weighed and immediately sealed. The sample is placed in the heating furnace of the Karl Fischer moisture analyzer and the moisture is released under 160℃ and dry nitrogen carrier gas conditions. The mass of the released moisture is determined by coulometric method and calculated according to "moisture content = measured moisture mass / PA6 slice mass × 100%". Each batch is measured in parallel 3 times.
[0079] 2. Breaking strength and elongation at break of PA6 short fibers
[0080] Each batch of PA6 short fibers was placed in an environment with a temperature of 20℃ and a relative humidity of 65% for 24 hours to equilibrate. Fifty single fibers were randomly selected from each batch and tensile tests were conducted using a single fiber tensile testing machine with a clamping distance of 20 mm and a tensile speed of 20 mm / min. The breaking load and breaking elongation of each fiber were measured, and the breaking strength was calculated based on the single fiber linear density. The results are expressed as cN / dtex, and the coefficient of variation of the breaking strength was also calculated.
[0081] Table 1 shows the experimental data for Examples 1 to 4 and Control Example 4.
[0082]
[0083] Combined with Example 1, Comparative Example 1, and Figure 1It can be seen that the longitudinal surface of the PA6 short fibers obtained in Example 1 is relatively smooth, with fewer attached particles and more uniform fiber thickness. Its cross-section is a near-cross shape with clear outline and complete branches, and the cross-sectional shape has good consistency. In contrast, in Control Example 1 without the addition of 6-aminohexanoic acid, the surface roughness of the obtained short fibers increased and more obvious particle agglomeration appeared. The size and branch symmetry of the near-cross-shaped cross-section decreased, and some cross-sections showed rounded or slightly collapsed. This indicates that the addition of 6-aminohexanoic acid for acid adsorption is beneficial to improving the dispersion state of titanium dioxide in the PA6 system, thereby improving the uniformity of the short fiber surface and the forming of irregular cross-sections.
[0084] In conjunction with Example 1 and Comparative Example 1, Figure 2 As can be seen, the PA6 short fibers obtained in Example 1 have a relatively smooth surface, fewer particulate agglomerates, and a complete and consistent near-cross-shaped cross-section. Their crystallization peak temperature, crystallization enthalpy, melting enthalpy, and crystallinity are 191.6℃, 59.2J / g, 62.4J / g, and 27.7%, respectively. In contrast, in Control Example 1, no 6-aminohexanoic acid was added, resulting in a rougher surface and more particulate agglomerates. Some branches of the near-cross-shaped cross-section were asymmetrical or slightly collapsed, and their crystallization peak temperature, crystallization enthalpy, melting enthalpy, and crystallinity decreased to 187.9℃, 51.7J / g, 54.8J / g, and 24.3%, respectively. The electron microscopy morphology and DSC results corroborate each other, indicating that 6-aminohexanoic acid, after acid adsorption and alkaline redispersion, can improve the dispersion state of titanium dioxide in the PA6 system, forming more uniform heterogeneous nucleation sites, promoting the orderly arrangement and crystallization of PA6 molecular chains, and improving the uniformity of the forming of shaped short fibers. The melting peak temperatures of the two methods are 221.8℃ and 220.9℃, respectively, with little difference, indicating that the treatment did not significantly change the melt transformation characteristics of PA6.
[0085] As can be seen from Examples 1-4 and Table 1, the PA6 chips obtained in Examples 1-4 had a moisture content of 0.0118%-0.0186%, all not exceeding 0.02%. The near-cross-shaped PA6 short fibers obtained from them had a breaking strength of 4.62-4.83 cN / dtex, a breaking elongation of 28.1%-29.6%, and a breaking strength coefficient of variation of 3.9%-4.7%. This indicates that within the range of carbon dioxide acidification pH, 6-aminohexanoic acid dosage, adsorption time, ammonia alkalization pH, and shear conditions specified in this application, PA6 nylon compositions with low moisture content and suitable for melt spinning can be obtained. The resulting short fibers have high breaking strength and breaking elongation, while the strength dispersion between individual fibers is small.
[0086] As can be seen from Example 1, Comparative Example 1, and Table 1, the moisture content of the PA6 chips in Example 1 and Comparative Example 1 were 0.0186% and 0.0190%, respectively, which were quite close. The breaking strength of the short fibers obtained in Example 1 was 4.62 cN / dtex, the elongation at break was 28.1%, and the coefficient of variation of breaking strength was 4.7%, while those in Comparative Example 1 were 3.89 cN / dtex, 24.2%, and 8.6%, respectively. Compared with Comparative Example 1, the breaking strength of Example 1 increased by approximately 18.8%, the elongation at break increased by approximately 16.1%, and the coefficient of variation of breaking strength decreased by approximately 45.3%. In Comparative Example 1, without the addition of 6-aminohexanoic acid, titanium dioxide mainly relies on pH adjustment and mechanical shearing for temporary dispersion, and is prone to re-agglomeration after entering the caprolactam polymerization system. In Example 1, with the addition of 6-aminohexanoic acid, 6-aminohexanoic acid can form a modified layer on the surface of titanium dioxide and form an interface with the PA6 molecular chain, reducing the agglomeration of titanium dioxide and the stress concentration points formed in the fiber, thereby improving the strength, elongation and uniformity of short fibers.
[0087] Combining Example 1, Comparative Example 2, and Table 1, it can be seen that the moisture content of PA6 chips in Example 1 and Comparative Example 2 is 0.0186% and 0.0192%, respectively, with little difference. The breaking strength and elongation at break of the short fibers obtained in Example 1 are 4.62 cN / dtex and 28.1%, respectively, which are higher than those of Comparative Example 2 (4.08 cN / dtex and 25.4%), representing increases of approximately 13.2% and 10.6%, respectively. Simultaneously, the coefficient of variation for breaking strength decreased from 7.4% to 4.7%, a reduction of approximately 36.5%. Although Comparative Example 2 added the same amount of 6-aminohexanoic acid, it did not pre-adjust the system to pH 4.5 by introducing carbon dioxide, thus limiting the adsorption amount and uniformity of 6-aminohexanoic acid on the titanium dioxide surface. Example 1, by acidifying with carbon dioxide, altered the surface sites of titanium dioxide and the ionization state of the carboxyl groups of 6-aminohexanoic acid, which facilitated the adsorption or coordination of 6-aminohexanoic acid with the titanium dioxide surface, thereby forming a more complete interface modification layer.
[0088] Combining Example 1, Comparative Example 3, and Table 1, it can be seen that the moisture content of PA6 chips in Example 1 and Comparative Example 3 were 0.0186% and 0.0195%, respectively, both at a low level. The breaking strength of the short fibers obtained in Example 1 increased from 3.67 cN / dtex in Comparative Example 3 to 4.62 cN / dtex, an increase of approximately 25.9%; the breaking elongation increased from 22.8% to 28.1%, an increase of approximately 23.2%; and the coefficient of variation of breaking strength decreased from 10.2% to 4.7%, a decrease of approximately 53.9%. In Comparative Example 3, ammonia was not introduced for alkalization after acidic adsorption treatment. However, under pH conditions of 4.5–4.6, the electrostatic repulsion between titanium dioxide particles was weak, and the loose aggregates formed during adsorption were difficult to maintain stable dispersion through simple shearing. In Example 1, ammonia was used to adjust the pH of the system to 8.0, enhancing the charge repulsion and hydration between modified titanium dioxide particles. Combined with shear dissociation of aggregates, this resulted in the titanium dioxide maintaining a better dispersion state before entering the caprolactam polymerization system. This indicates that the acidic stage is mainly used to promote the adsorption of 6-aminohexanoic acid, while the alkaline stage is mainly used to restore and stabilize particle dispersion. The two stages need to be implemented in a coordinated manner, first acidifying the adsorption and then alkalizing the dispersion.
[0089] As can be seen from Example 1, Comparative Example 4 and Table 1, the moisture content of PA6 chips in Example 1 was 0.0186%, which was lower than that of Comparative Example 4 (0.0213%). The breaking strength and elongation at break of the short fibers obtained in Example 1 were 4.62 cN / dtex and 28.1%, respectively, while those in Comparative Example 4 were 4.15 cN / dtex and 25.9%, respectively, representing an increase of approximately 11.3% and 8.5%, respectively. The coefficient of variation of the breaking strength in Example 1 was 4.7%, which was approximately 31.9% lower than that of Comparative Example 4 (6.9%). In Comparative Example 4, hydrochloric acid and sodium hydroxide were used to adjust the pH. The sodium and chloride ions formed by their neutralization would enter the caprolactam polymerization system with the titanium dioxide dispersion that had not undergone solid-liquid separation and washing, increasing the residual non-volatile ions in the system and potentially affecting the dispersion stability of titanium dioxide, the PA6 polymerization process, and the hygroscopicity of the chips. In Example 1, carbon dioxide and ammonia were used to adjust the pH. The resulting ammonium carbonate or ammonium bicarbonate components could decompose and escape during the subsequent heating polymerization process, reducing the residual non-volatile salts. Therefore, it was more suitable to combine with the process of directly adding the surface-modified titanium dioxide dispersion to the polymerization reactor without separation.
[0090] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A PA6 nylon composition for use in staple fiber fabrics, characterized in that, The composition includes PA6 resin and surface-modified titanium dioxide dispersed in the PA6 resin, wherein the titanium dioxide accounts for 2% of the total mass of the PA6 nylon composition.
2. The PA6 nylon composition for staple fiber fabrics according to claim 1, characterized in that, The titanium dioxide is anatase titanium dioxide.
3. A method for preparing a PA6 nylon composition for staple fiber fabrics according to any one of claims 1 to 2, characterized in that, Includes the following steps: S1. Mix titanium dioxide and water, with the total mass of titanium dioxide and water being 100%, the mass percentage of titanium dioxide being 30% and the mass percentage of water being 70%, and stir at 60°C to obtain a titanium dioxide aqueous dispersion system; S2. Carbon dioxide is introduced into the titanium dioxide aqueous dispersion system to adjust the pH of the titanium dioxide aqueous dispersion system to 4.5-5.2; 0.3%-0.8% of 6-aminohexanoic acid by mass of the titanium dioxide is added, and adsorption treatment is carried out at 60°C. S3. Stop the carbon dioxide flow, introduce ammonia into the adsorption-treated titanium dioxide aqueous dispersion system, adjust its pH to 8.0-9.0, and then perform shear dispersion to obtain surface-modified titanium dioxide aqueous dispersion. S4. Before the caprolactam starts heating, the surface-modified titanium dioxide aqueous dispersion is added to the caprolactam polymerization reactor. The amount of the surface-modified titanium dioxide aqueous dispersion added is determined according to 2% of the total mass of the titanium dioxide in the PA6 nylon composition. The surface-modified titanium dioxide aqueous dispersion and caprolactam are heated together and polymerized at 260°C to obtain the PA6 polymer. S5. The PA6 polymer is sequentially pelletized, extracted, and dried to obtain the PA6 nylon composition.
4. The preparation method according to claim 3, characterized in that, In step S2, after adding the 6-aminocaproic acid, the mixture is stirred at 60°C for 60–120 min.
5. The preparation method according to claim 4, characterized in that, In step S3, the rotation speed of the shearing dispersion is 1000-2000 r / min, and the shearing dispersion time is 20-40 min.
6. The preparation method according to claim 5, characterized in that, The surface-modified titanium dioxide aqueous dispersion obtained in step S3 is added directly to the caprolactam polymerization reactor without solid-liquid separation and drying.
7. The preparation method according to claim 6, characterized in that, In step S4, the polymerization temperature is 260℃, and the highest temperature of the material during the polymerization process is below 270℃.
8. The preparation method according to claim 7, characterized in that, In step S5, hot air circulation is used for drying. The drying temperature is 85-110℃ and the drying time is 5-6 hours. The moisture content of the dried PA6 slices is not higher than 0.02%.